A Study on the Philosophical Dimension of Ritual Music of Mahayana Buddhism in Chinese Han Tradition--A Case Study of Huayan Temple in Chongqing, China - Le , Dai; Jamnongsarn, Surasak; Rodsakan, Tepika (Journal of Roi Kaensarn Academi, 2023)
This paper analyzes and studies the ritual music of Chinese Mahayana Buddhism, using Huayan Temple in Chongqing as an example, using field investigation, music data analysis, and other research techniques.Huayan Temple's Buddhist ritual music is not only an essential component of Chinese Buddhist music but also a significant manifestation of Chinese traditional culture and philosophy Huayan Temple's Buddhist ritual music has extensive and profound connotations and significance, which provides a means for modern people to pursue inner serenity and tranquility and has significant cultural and practical value.Through the preservation and transmission of Buddhist ritual music at Huayan Temple, it can radiate with new vigor and vitality into contemporary society and infuse fresh energy into the transmission and innovation of traditional culture.Therefore, it is of great practical and historical importance to continue researching and promoting the Buddhist ritual music of the Huayan Temple in order to promote the transmission and development of traditional culture as well as the sublimation of human spiritual civilization.